Public Prosecution Service and its role in supervision of decentralized public administration in Slovakia - Jaroslav Mihálik (Public Policy and Administration, 2018)
The system of decentralized public administration creates a vital environment for better interaction between the state, its sub units and citizens. Despite all benefits, the growing nature of bureaucratic procedures and power distribution seem to attract more attention, mainly from the reasons of unprecedented mechanisms of control. The aim of the paper is to demonstrate the potential of Public Prosecution Service in Slovakia to control the decentralized public administration being provided with a statutory power to monitor the field of public administration as a whole and whether the competence to exercise supervision over the law-abidingness should not be entrusted to other public authorities, such as the Public Defender of Rights. The paper is conceived as a case study of methods of prosecutorial supervision and their practical application in Slovakia.